ANALISIS PENGARUH LOKASI DAN PELAYANANTERHADAP MINAT MENABUNG DI BPRS AMPEK ANGKEK CANDUANG ( Studi Kasus Pedagang Pasar Aur Kuning Bukittinggi) - Anwar Sholihin; Bunga Rahma Aulia (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The problem of this research is how to analyze the influence of location and type of service on interest in saving at BPRS Ampek Angkek Canduang. Case Study of Aur Kuning Market Traders, Bukittinggi. Meanwhile, the purpose of this study was to analyze the effect of location and type of service on interest in saving at BPRS Ampek Angkek Canduang. A case study of traders at Pasar Aur Kuning, Bukittinggi. This study uses a quantitative approach with data collection techniques, namely, a questionnaire (questionnaire) and observation. While the data analysis technique used multiple linear regression analysis, namely Y = a + bx1 + bx2, validity test, multicollinearity test, normality test, heteroscedasticity test, autocorrelation test T-Test, F test and coefficient of determination, multiple correlation. The results of the analysis carried out using SPSS 16.0 software resulted in an output analysis showing that significantly the variables owned, namely the location variable (X1) and service (X2) have a contribution to the interest in saving (Y) of market traders in Aur kuning, Bukittinggi, with a value of Y = 5.382 + 0.339x1 + 0.556 x2 and the significant value is 0.000 < 0.005. Thus, it can be seen that the independent variables, namely location and service, have a positive effect on the interest in saving (Y) of market traders at Aur Kuning Bukittinggi, and is a positive influence which indicates a good relationship or good influence.